Cardiovascular Disease in Women: What the Radiologist Needs to Know - Sommer, Oliver Josef; Hergan, Klaus (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2022)
Background Sex-specific disparities are well documented for cardiovascular disease (CVD). There are differences in physiology and pathophysiology, pain perception, spectrum of disease, risk, therapeutic aspects, prognosis, and outcome. CVD represents a broad spectrum of disorders. This review focuses on cardiovascular and cardiac pathology.Method This review summarizes the current state of the literature on cardiovascular disease in women from a radiological viewpoint. It aims to provide a deeper understanding of these differences and thereby alerts the reader to the potential of CT and MRI for diagnosing CVD in women. Special attention is paid to disparities in the underlying physiological and pathophysiological processes, clinical presentation, and the quality of care to provide a deep understanding of the topic. Cardiovascular and cardiac pathologies with a sex-specific pattern of disease are presented and typical CT and MRI findings are arranged and illustrated with imaging findings.Results and Conclusion Sex-specific differences are not only sex hormonal in nature but are rooted in the epigenome and encompass a multitude of physiological systems. In fact, cardiovascular disease shows sex-specific characteristics spanning from incidence to clinical presentation, course of disease, and prognosis. This is of significance regarding pretest probabilities, the power of tests, imaging strategies, and interpretation of imaging results. Key sex-specific issues encompass obstructive and non-obstructive coronary artery disease (CAD), microvascular angina, myocardial infarction with non-obstructive CAD, and coronary artery dissection. Sex-specific patterns are also noted in myocardial disease and heart failure such as pregnancy-related heart disease, Takotsubo syndrome, and anthracycline-induced cardiotoxicity.Key points:
Keywords: cardiac; heart; CT; CT angiography; MR imaging